Pengaruh Jumlah Wisatawan, Tingkat Hunian Hotel, dan Pengeluaran Konsumsi Rumah Tangga terhadap Penerimaan Pajak Hotel Kota Banjarmasin - Nur Ainun Jariah; Muzdalifah Muzdalifah (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to measure the strength of the relationship between the number of tourists, hotel occupancy rates, and household consumption expenditures on hotel tax revenue in Banjarmasin City. The research scope is hotel tax in Banjarmasin City using multiple linear regression analysis with quantitative descriptive data collection techniques from secondary data sourced from literature (literature) and official data.This research results in a joint influence between the number of tourists, hotel occupancy rates, and household consumption expenditures on hotel tax revenue in Banjarmasin City. Meanwhile, only partially the number of tourists has a positive and significant effect. In line with the test results, the most dominant influencing variable is the number of tourists.